PENGARUH INVESTASI INFRASTRUKTUR TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Ahmad Taufik Yahya; Sofyan Syahnur (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2020)
AbstractThis study aimed to find out the effect of infrastructure investment on economic growth in Indonesia. The method used in this study is a quantitative analysis method using the Autoregressive Distributed Lag (ARDL) model. The data used in this study are time series for the period from 1993 to 2017. This study are used the variables in Indonesia's economic growth, domestic investment and foreign investment in the water, electricity and gas infrastructure sector. The results shows that the domestic investment (PMDN) of the water, electricity and gas sector in the previous year had a value above 0.05 units, then this variable had a negative effect on Indonesia's economic growth, whereas for the last two, three and four years had a value below 0.05 unit, then this variable has a positive effect on Indonesia's economic growth. the foreign investment (PMA) of the water, electricity and gas sector in the last year and the last two years has a value below 0.05 units, then this variable has a positive effect on Indonesia's economic growth, meanwhile,in the last three and four years has a value above 0.05 units, then this variable has a negative effect on Indonesia's economic growth.Keywords: Infrastructure, Economic Growth, Domestic Investment, foreign investment, Indonesia